2019
DOI: 10.1093/femspd/ftz055
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil and monocyte receptor expression in patients with sepsis: implications for diagnosis and prognosis of sepsis

Abstract: Understanding the complex immune responses in sepsis is crucial to provide insight into the clinical syndrome. We evaluated the changes in the surface receptors of the cells of innate immunity, neutrophils and monocytes, in patients with sepsis. Since sepsis remains a clinical challenge, we aimed to assess the significance of altered receptor expression in diagnosis and prognosis. Critically ill patients with sepsis (n=31) were investigated for the expression of receptors for IgG heavy chain CD64 and CD16 on n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 39 publications
2
16
1
Order By: Relevance
“…We also evaluated the performance of the continuous nCD64 index in predicting death, and a significant association between the baseline nCD64 index and inhospital death was observed (OR: 2.18, 95% CI: 1.02-4.74), which is consistent with previous studies in neonates (12,20). In this study, a positive significant association between nCD64 index decline and death was observed (OR: 1.31, 95% CI: 1.07-1.58) in the crude model.…”
Section: Discussionsupporting
confidence: 87%
“…We also evaluated the performance of the continuous nCD64 index in predicting death, and a significant association between the baseline nCD64 index and inhospital death was observed (OR: 2.18, 95% CI: 1.02-4.74), which is consistent with previous studies in neonates (12,20). In this study, a positive significant association between nCD64 index decline and death was observed (OR: 1.31, 95% CI: 1.07-1.58) in the crude model.…”
Section: Discussionsupporting
confidence: 87%
“…In a recent study with a small sample size, authors did not find alterations of monocytes in patients with sepsis. in addition, they reported that monocyte CD64 expression was not related to mortality risk in this patient population [243]. This is in accordance with our results (unpublished data) from our investigation of 86 critically ill patients with secondary sepsis.…”
Section: Monocyte Cd64 Expressionsupporting
confidence: 93%
“…The group consequently concluded that early flow cytometric measurements of CD64 +ve granulocytes could help clinicians to target patients at high risk of clinical deterioration [242]. In one study, expression of CD64 on neutrophils was specific for discriminating patients with sepsis but showed weak sensitivity [243].…”
Section: Neutrophil Cd64 Expressionmentioning
confidence: 99%
“…In addition, it also demonstrated that CD64 was significantly elevated in monocyte/macrophage cells, which was consistent with previously published studies ( 29 , 30 ). However, controversy remains about whether CD64 expression on monocytes can be a diagnostic and prognostic biomarker for sepsis ( 31 ). Some researchers found that simultaneously analyzing CD64 expression for both types of cells can improve the accuracy of diagnosis ( 32 ).…”
Section: Discussionmentioning
confidence: 99%